Mawqi‘ al-Ru’yah al-Kawniyyah al-Islāmiyyah fī al-Tajdīd al-Ḥaḍārah al-Mu‘āṣir - BarghÅ«th, â€˜Abd al-AzÄ«z (Jurnal Usuluddin, 2002)
The present paper aspires towards exploring the position and role of the Islamic worldview on the contemporary civilizational reconstruction. There is still a problem in demarcating the dynamic socio-cultural function of the Islamic worldview in the process of re-inventing the new Islamic personality, culture and Ummah. As such, the Islamic worldview should regain its function as a pivotal catalyst of the process of civilizational reconstruction. The paper follows the textual analysis in order to disentangle the structural and functional dimensions of the Islamic worldview. In this regard, it is made clear that the Islamic worldview is meant for the re-invention of man, society, culture and civilizational values of Islam. On the other hand, the paper states that there should be a critical review of the existing theories on the Islamic civilization reconstruction. In this respect, a new multi-dimensional and multi-civilizational theory of reconstruction is barely required. As such, the Islamic worldview should become the deriving force and the cementing factor that can bring back the sense of efficacy, consistency and unity to the Muslim activities and processes of reconstruction. Finally, the paper calls for the fresh and sytematic review of the existing works and literatures on the issues pertaining to the reconstruction of the Ummah and the position of the Islamic worldview. Here, the first step should be the re-thinking and reinventing of the civilizational dimension of the Islamic worldview and the Islamic reconstruction process.